PENGEMBANGAN WEBSITE EDUKATIF MADANI (MEDIA DAKWAH NILAI ISLAM) SEBAGAI MEDIA PEMBELAJARAN PAI KELAS III SEKOLAH DASAR - Nur Aeni, Ani; Amalia, Ghina; Siti Rosmawati, Ai; Ramadhani, Ghalbia; Ramadhani, Revina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the need for innovative learning media in Islamic Religious Education (IRE) in elementary schools, specifically to help students understand abstract moral values and enhance their motivation to learn. This study aims to develop and evaluate the feasibility and effectiveness of the MADANI (Media Dakwah Nilai Islam) Educational Website as a learning medium for third-grade elementary school students. The method used is Design and Development (D&D) based on the ADDIE model, which comprises five stages: analysis, design, development, implementation, and evaluation. Data were collected through interviews, observations, validation sheets, tests (pre-tests and post-tests), and student response questionnaires. The results indicate that the MADANI website is highly feasible based on expert validation regarding content, design, and ease of use. Implementation results show a significant improvement in student learning outcomes, evidenced by higher post-test scores compared to pre-test scores. Furthermore, student responses to the website’s use were highly positive, indicating increased motivation, engagement, and interest in learning. Thus, the MADANI website has proven to be an innovative and effective digital learning medium that supports meaningful learning and helps students understand and apply moral values in their daily lives.